2020
DOI: 10.1021/acs.jpcb.9b11947
|View full text |Cite
|
Sign up to set email alerts
|

How Does Addition of Lithium Salt Influence the Structure and Dynamics of Choline Chloride-Based Deep Eutectic Solvents?

Abstract: In recent times, deep eutectic solvents (DESs) have emerged as an environment-friendly alternative to both common organic solvents and ionic liquids (ILs). The present study has been undertaken with an objective to understand the intermolecular interaction, structural organization, and dynamics of two DES systems in the absence and presence of lithium salt so that the potential of these mixtures in electrochemical application is realized. For this purpose, the steady-state, time-resolved fluorescence, electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 74 publications
6
25
0
Order By: Relevance
“…Overall, the Li salt causes an increase in viscosity (with LiPF6 < LiTFSI, Table 3), decrease in conductivity (Table 3), and decrease in 1 H diffusion values (for instance from 2.2 x 10 -11 m 2 s -1 in neat ChCl:EG to 0.65 x 10 -11 m 2 s -1 after addition of LiTFSI at 0.3 mole fraction). 175,176 In line with previous observations, EG-based systems exhibited lower viscosities, higher diffusivities and higher conductivity than systems based on G or LA, due to the presence of a less extensive hydrogen bonding network between ChCl and EG as well as within EG molecules. 175,176 ChCl:EG containing Li salts has then the potential to act as a discrete medium for electrochemical applications.…”
Section: Lithium Salt-added Type III Desssupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, the Li salt causes an increase in viscosity (with LiPF6 < LiTFSI, Table 3), decrease in conductivity (Table 3), and decrease in 1 H diffusion values (for instance from 2.2 x 10 -11 m 2 s -1 in neat ChCl:EG to 0.65 x 10 -11 m 2 s -1 after addition of LiTFSI at 0.3 mole fraction). 175,176 In line with previous observations, EG-based systems exhibited lower viscosities, higher diffusivities and higher conductivity than systems based on G or LA, due to the presence of a less extensive hydrogen bonding network between ChCl and EG as well as within EG molecules. 175,176 ChCl:EG containing Li salts has then the potential to act as a discrete medium for electrochemical applications.…”
Section: Lithium Salt-added Type III Desssupporting
confidence: 89%
“…175,176 In line with previous observations, EG-based systems exhibited lower viscosities, higher diffusivities and higher conductivity than systems based on G or LA, due to the presence of a less extensive hydrogen bonding network between ChCl and EG as well as within EG molecules. 175,176 ChCl:EG containing Li salts has then the potential to act as a discrete medium for electrochemical applications. In particular ChCl:EG + LiPF6 0.5 M displayed a ionic conductivity of 7.95 mS cm −1 and viscosity of 88.4 mPa s at room temperature, together with a reasonable electrochemical stability against glassy carbon as the working electrode (3.5 V).…”
Section: Lithium Salt-added Type III Desssupporting
confidence: 89%
See 1 more Smart Citation
“…To provide pathways for broadening the DES applications, elucidation of the molecular level interactions, structural organization and structure–property relationship in DESs is certainly desirable. Different experimental and computational techniques have evidenced a nanoscopic heterogeneous environment in DESs: X-ray structural analysis, neutron scattering, vibrational spectroscopy, 9–11 time-resolved fluorescence, 12 nuclear magnetic resonance (NMR), 12 spin-probe electron paramagnetic resonance (EPR), 12–14 pulse-field gradient (PFG) nuclear magnetic resonance (NMR), 15–17 molecular dynamic (MD) simulations, 9,18 and others.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Since the starting materials for the preparation of DESs are relatively cheaper as compared to ILs, large scale preparation of DESs is possible for their use in various fields such as electrochemistry, 19,20 synthesis, 21 catalysis, 18,22 nanotechnology, 23,24 and gas adsorption. 25 Some notable experimental techniques like fluorescence, [26][27][28][29][30][31][32] small angle neutron scattering, 33,34 NMR diffusion [35][36][37][38][39] and theoretical studies based on molecular dynamics (MD) simulation [40][41][42][43][44][45] have been used to explore the microscopic structural organisation and dynamics of DESs and RTILs independently. Atkins and co-workers 17 suggested that ILs have huge structural diversity depending on the nature of ions as well as their selforganisation into ion pairs, ions' crystal lattice, H-bonding network and micellar domains.…”
Section: Introductionmentioning
confidence: 99%